2006
DOI: 10.1063/1.2372464
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of the fan instability: Electron flux relaxation

Abstract: This paper presents some relevant simulation results on the interaction between electrostatic waves and suprathermal electron fluxes at anomalous cyclotron and Landau resonances. In particular, the case of a dense and continuous wave spectrum is studied. It is shown that, after the waves excited by the fan instability at anomalous cyclotron resonances have reached a first saturation stage due to particle trapping, the process of “dynamical resonance merging” takes place, which leads to a strong amplification o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…The numerical simulation results and the analytical developments discussed below are all based on a threedimensional theoretical model [19][20][21][22] that describes the quasilinear evolution of electrostatic waves resonantly interacting with particles in a magnetized plasma ͑nonlinear wave-wave interactions are neglected compared to wave-particle ones͒. In this model, we suppose that the plasma electrons can be divided in two groups: a thermal bulk of density n 0 and a suprathermal flux of resonant particles with a much smaller density: n res Ӷ n 0 .…”
Section: Theoretical Model and Numerical Codementioning
confidence: 99%
See 2 more Smart Citations
“…The numerical simulation results and the analytical developments discussed below are all based on a threedimensional theoretical model [19][20][21][22] that describes the quasilinear evolution of electrostatic waves resonantly interacting with particles in a magnetized plasma ͑nonlinear wave-wave interactions are neglected compared to wave-particle ones͒. In this model, we suppose that the plasma electrons can be divided in two groups: a thermal bulk of density n 0 and a suprathermal flux of resonant particles with a much smaller density: n res Ӷ n 0 .…”
Section: Theoretical Model and Numerical Codementioning
confidence: 99%
“…As one can separate the Hamiltonian ͑1͒ as H = H 1 + H 2 , where H 1 = ͚ p=1 N ͓P p + eA 0 ͑r p ͒ / c͔ 2 / 2m e , the symplectic operator 23,24 L͑⌬t͒ = L 1 ͑⌬t / 2͒L 2 ͑⌬t͒L 1 ͑⌬t / 2͒ + o(͑⌬t͒ 3 ) of order 2 in time step can be used for advancing the Hamiltonian H; L 1 and L 2 are canonical transformations applying to H 1 and H 2 , respectively. 21,22 The model allows one to choose arbitrary sets of waves ͑k , k ͒ for which the periodicity conditions have to be verified, i.e., k x,y,z L x,y,z / 2 = ± 1 , ± 2. . ., where ͓L x , L y , L z ͔ is a three-dimensional spatial simulation box of volume V = L x L y L z .…”
Section: ͑5͒mentioning
confidence: 99%
See 1 more Smart Citation
“…It assumes that the plasma particle velocity distribution can be split into (i) a thermal bulk containing almost all ions and supporting the waves' dispersion and propagation, and (ii) the resonant ions, which are involved in intense energy exchanges with the waves [27]. Whereas the oscillations of the nonresonant ions of the bulk in the waves' potentials can be considered using the linear approach, the motion of the resonant particles is essentially nonlinear and described by the Newton-Lorentz equations.…”
Section: Theoretical and Numerical Modellingmentioning
confidence: 99%
“…Then, the anisotropic character of the parallel velocity distribution is the cause of the resonant wave generation at the anomalous cyclotron resonances. Note that fan instability due to electron distributions [20][21][22][23][24][25][26][27] physics as well as in tokamak plasmas [28], where suprathermal tails of electrons can be created during the current drive [29,30]. Some authors [31] explain the perpendicular heating of ion beams observed above the auroral terrestrial acceleration region by the excitation of ion acoustic waves generated by the ion distributions owing to the fan instability; performing calculations in the frame of the quasilinear theory of weak turbulence, they obtain an estimate of the heating rate, which is consistent with satellite observations [9,19] and that they compare with numerical simulations performed in 1D geometry, all waves propagating in the same quasiperpendicular direction (see also [32]).…”
Section: Introductionmentioning
confidence: 99%